Risk Management in Global Supply Chains: An Empirical Study of Multinational Corporations - Degdo Suprayitno (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
In the era of globalization and supply chain complexity, risk management has become crucial for multinational companies to maintain operational resilience. This research identifies gaps in the understanding and implementation of effective risk management strategies in the sector. This research aims to analyze the influence of risk identification capabilities and risk mitigation strategies on supply chain resilience in multinational companies. A quantitative approach was used with a 5-point Likert scale-based questionnaire survey to collect data from executives and managers at MAP. Multiple linear regression analysis was applied to test the relationship between independent and dependent variables. The findings show that risk identification capabilities and risk mitigation strategies have a significant influence on supply chain resilience, with respective contributions of 41.8% and 31.4%. These results emphasize the importance of proactive risk management in improving operational resilience. This research makes a significant contribution to risk management theory and practice in the retail sector, with recommendations for adopting a systematic approach in risk mapping and developing adaptive mitigation strategies.